Composite insulator and preparation method thereof
By introducing nanosilicon dioxide, nanoalumina and semi-carbonized straw powder into the umbrella skirt material of composite insulators, an efficient charge trap and energy dissipation center is formed, which solves the problem of poor corona resistance performance of the umbrella skirt, and significantly improves the life and reliability of the insulator.
Patent Information
- Application Number
- CN202411699398.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The corona resistance performance of the composite insulator umbrella skirt is poor, resulting in frequent local discharge phenomena, which in turn causes insulation breakdown and reduces the life and reliability of the insulator.
Nanosilicon dioxide and nanoalumina reinforced umbrella skirt materials are used to form efficient charge traps and energy dissipation centers to increase the interface area between EPDM and nanoparticles, form a discharge channel network, and disperse the discharge energy by using the conductivity and resistivity of semi-carbonized straw powder.
It significantly improves the corona resistance performance of the umbrella skirt, reduces the risk of material deterioration and insulation breakdown caused by local discharge, extends the service life of composite insulators, and improves its overall reliability and safety.
Smart Images

Figure CN119181551B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of insulators, and more specifically, to a composite insulator and a preparation method thereof. Background Art
[0002] Composite insulators, also known as synthetic insulators, are a special type of insulation control. They are a multi-insulation structure composed of continuous layers of different insulating materials. They are new safety insulation materials used to replace traditional insulators and other electrical insulation devices. Composite insulators play the role of supporting conductors in overhead transmission lines. Composite insulators are usually composed of a glass fiber resin core rod and an organic material sheath and shed skirt. The shed skirt is set on the surface of the core rod. The main function of the shed skirt is to disperse the accumulated water or dirt on the surface of the insulator in the outdoor environment, thereby reducing the risk of forming a conductive channel on the surface of the insulator and causing a flashover accident.
[0003] In the related art, silicone rubber is generally used as the shed of composite insulators. Since composite insulators work in high electric field environments such as high-voltage transmission lines, partial discharge is prone to occur on the surface and near the composite insulator, that is, visible blue or purple flashes are produced on the surface of the composite insulator or near the electrode, accompanied by a weak popping sound. Since the corona resistance of pure silicone rubber materials is poor, it is difficult to quickly disperse the discharge energy generated by partial discharge. Therefore, the partial discharge phenomenon will cause the shed on the surface of the composite insulator to gradually deteriorate, and even cause insulation breakdown problems, which will lead to a reduction in the life and reliability of the composite insulator.
[0004] In summary, the shed of the composite insulator in the related art has the problem of poor corona resistance. Summary of the invention
[0005] In order to improve the corona resistance of the shed and thus comprehensively improve the reliability of the composite insulator, the present application provides a composite insulator and a preparation method thereof.
[0006] The composite insulator provided in this application adopts the following technical solution:
[0007] A composite insulator, comprising:
[0008] A core tube, wherein the core tube is filled with polypropylene foam material;
[0009] An end flange, the end flange is located at the end of the core tube and is coaxially connected to the core tube, and the end flange is used to seal the end of the core tube;
[0010] An umbrella skirt is wrapped around the surface of the core tube;
[0011] The umbrella skirt comprises the following raw materials in parts by weight:
[0012] 30-50 parts of EPDM rubber;
[0013] 5-8 parts of fiber-powder bonding material;
[0014] 8-10 parts of β-alanine solution;
[0015] 2-5 parts of semi-carbonized straw powder;
[0016] Nano silicon dioxide 0.1-0.3 parts;
[0017] Nano-alumina 0.1-0.3 parts;
[0018] 1-3 parts of vulcanizing agent;
[0019] 1-3 parts of compatibilizer;
[0020] The fiber-powder bonding material is obtained by bonding polyester fiber to the surface of tourmaline powder;
[0021] The semi-carbonized straw powder is obtained by subjecting the straw to a low-oxygen heating treatment at a semi-carbonization temperature, followed by crushing and screening.
[0022] By adopting the above technical solution, nano-silicon dioxide and nano-alumina are added to the raw materials of the shed, and the nano-silicon dioxide and nano-alumina have a higher specific surface area, so that the interface area between the EPDM rubber and the nanoparticles can be increased. The increased interface area not only enhances the interaction force between the materials, but also can serve as an effective charge trap or energy dissipation center, which can quickly disperse and dissipate the energy generated during the partial discharge process, thereby effectively inhibiting the accumulation of charges and the expansion of discharge, thereby greatly improving the corona resistance of the shed. At the same time, by adding fiber-powder bonding materials, a discharge channel network can be formed inside the EPDM rubber, so that the discharge energy is released along the discharge channel network, significantly reducing the direct impact and damage of the energy on the material structure. Further, by bonding polyester fiber on the surface of tourmaline powder, since polyester fiber has better thermal conductivity, the conductivity of the discharge channel can be further enhanced, thereby improving the dispersion effect of the shed material on the energy generated by the partial discharge, improving the corona resistance of the shed material, and then reducing the problem of rapid degradation or even insulation breakdown of the shed material due to partial discharge. As an organic compound, β-alanine has a van der Waals force between its molecular structure and the oxygen-containing functional groups on the surface of the polyester fiber, which helps the β-alanine molecules to form a uniform covering layer on the surface of the fiber-powder adhesive material, thereby having a lubricating and dispersing effect on the fiber-powder adhesive material based on tourmaline powder, thereby improving the uniformity of the dispersion of the fiber-powder adhesive material in the EPDM rubber, avoiding the problems of agglomeration and uneven distribution of the fiber-powder adhesive material, and ensuring the effective construction of the discharge channel in the EPDM rubber, and promoting the balanced improvement of the overall performance of the material, so that the shed material can exhibit more stable and reliable electrical performance when subjected to partial discharge.
[0023] By adding semi-carbonized straw powder, the processed semi-carbonized straw powder has a certain resistivity and a certain conductivity. In the process of preparing the shed, the semi-carbonized straw powder is dispersed on the discharge channel network path. When the local discharge current is released along the conductive channel network, the semi-carbonized straw powder has a certain conductivity, which helps the discharge current to be transmitted and released along the discharge channel network. At the same time, since the semi-carbonized straw powder has a certain resistivity, the discharge current will generate resistance heat when passing through the semi-carbonized straw powder, thereby converting part of the electrical energy into thermal energy to achieve energy dissipation. The semi-carbonized straw powder can gradually dissipate the discharge energy in the process of transmission and release along the conductive channel network, reducing the direct impact of the discharge energy on the rubber matrix, thereby helping to synergistically improve the corona resistance of the shed material with the fiber-powder bonding material. At the same time, the semi-carbonized straw powder after semi-carbonization treatment has higher density, hardness and strength. The semi-carbonized straw powder is added to the shed material as a reinforcing phase to form a tighter microstructure, thereby effectively improving the strength of the shed material. The reinforcing effect of the semi-carbonized straw powder enables the shed material to better resist deformation and damage when subjected to external forces.
[0024] In summary, this technical solution successfully constructs an efficient and stable corona-resistant system by introducing raw materials such as nano-silicon dioxide, nano-alumina, fiber-powder bonding materials, semi-carbonized straw powder and β-alanine solution. It not only significantly improves the corona resistance of the shed, but also effectively reduces the risk of rapid material degradation and insulation breakdown caused by partial discharge, thereby extending the service life of the composite insulator and improving the overall reliability and safety of the composite insulator.
[0025] Optionally, the fiber-powder bonding material is prepared by the following method:
[0026] a. Immerse the tourmaline powder in the HF solution, heat it to 60-70°C, stir and react for 3-5 hours, then filter the mixed solution, take the solid phase and dry it to obtain the pretreated powder;
[0027] b. Add the pretreated powder and polyester fiber to the acrylic adhesive for ultrasonic treatment, then heat to 40-50°C, stir for 2-3 hours, filter, and cure the solid phase at 50-60°C for 1-2 hours to obtain a fiber-powder bonding material.
[0028] By adopting the above technical solution, the surface of the tourmaline powder is etched by HF solution, which can improve the roughness of the tourmaline powder surface, help to enhance the interaction between the tourmaline powder and the polyester fiber and the acrylic adhesive, thereby helping to improve the bonding stability of the polyester fiber on the tourmaline powder surface, add the pretreated powder and polyester fiber to the acrylic adhesive for ultrasonic treatment, the energy of the ultrasonic wave can destroy the agglomerate, promote the uniform dispersion of the powder and fiber in the adhesive, and cure at 50-60°C for 1-2h, which can further promote the curing reaction of the adhesive, make the bonding interface more stable and reliable, and help to disperse the discharge energy to a larger area. The fiber-powder bonding material prepared by the above method has good stability, thereby effectively improving the corona resistance of the umbrella skirt material.
[0029] Optionally, the tourmaline powder is preferably calcium magnesium tourmaline powder, and the average particle size of the calcium magnesium tourmaline powder is 700 μm.
[0030] By adopting the above technical solution, calcium magnesium tourmaline powder is a substance containing silicate and calcium magnesium, the main components of which are calcium silicate and magnesium silicate. Calcium silicate can undergo double decomposition reaction with HF solution under heating and stirring conditions, but magnesium silicate, due to its relatively low chemical activity, shows a certain inertness in the reaction with HF solution and is not easy to react with HF solution. The above material characteristics enable calcium magnesium tourmaline powder to maintain an appropriate etching rate when in contact with HF solution, which is neither too intense nor too weak. Moderate etching treatment gives the surface of calcium magnesium tourmaline powder an ideal roughness, which is conducive to enhancing the physical bite force and chemical bonding force between calcium magnesium tourmaline powder and polyester fiber and acrylic adhesive, and also significantly improves the stability and reliability of the bonding interface. It is conducive to improving the corona resistance and overall stability of the umbrella skirt material.
[0031] Optionally, the mass concentration of the HF solution in step a is 15%-18%.
[0032] Optionally, in step b, the mass ratio of the pretreated powder to the polyester fiber is 1:(0.7-1).
[0033] By adopting the above technical solution, the tourmaline powder and polyester fiber in the above ratio range help to improve the bonding stability of the polyester fiber, thereby improving the overall performance of the fiber-powder bonding material.
[0034] Optionally, the semi-carbonized straw powder is prepared by the following method:
[0035] The straw is heated at 200-210°C and an oxygen concentration of 1%-5% for 2-3 hours, and then the heated straw is crushed and sieved to obtain semi-carbonized straw with an average particle size of 200 μm.
[0036] By adopting the above technical solution, by precisely controlling the heating temperature and oxygen concentration, it can be ensured that the straw will not be over-carbonized or under-carbonized during the semi-carbonization process. The appropriate degree of carbonization makes the semi-carbonized straw powder have both a certain resistivity and a certain conductivity. The semi-carbonization process achieves a good balance between the two, thereby achieving the release and dissipation of partial discharge energy.
[0037] Optionally, the mass concentration of the β-alanine solution is 5%-12%.
[0038] Optionally, the vulcanizing agent is selected from dicumyl peroxide.
[0039] Optionally, the compatibilizer is selected from ethylene vinyl acetate.
[0040] The present application also provides a method for preparing a composite insulator, which adopts the following technical solution:
[0041] A method for preparing a composite insulator comprises the following steps:
[0042] S1, put EPDM rubber, fiber-powder bonding material, semi-carbonized straw powder, nano-silicon dioxide and nano-alumina into a high-speed mixer, mix for 5-8 minutes, then add β-alanine solution, vulcanizing agent and compatibilizer into the high-speed mixer, and continue mixing for 3-5 minutes to obtain a premix;
[0043] S2, feeding the premix into an internal mixer, performing plasticizing at a temperature of 190-200° C. to obtain a rubber mixture, and then feeding the premix into an extruder to form a shed preform, and then adding the shed preform into a vulcanizer, performing vulcanization treatment at a temperature of 150-160° C. to obtain a shed;
[0044] S3. Fill the core tube with polypropylene foam material, and then seal both ends of the core tube with end flanges. Then clean the surface of the core tube, and then evenly apply adhesive on the surface of the core tube. Then cover the core tube with umbrella skirts and compact it. After natural drying, the composite insulator is obtained.
[0045] In summary, this application has the following beneficial effects:
[0046] 1. The present application introduces nano-silicon dioxide and nano-alumina into the shed material. The two nanoparticles of nano-silicon dioxide and nano-alumina effectively expand the interface contact area with EPDM rubber by virtue of their ultra-high specific surface area, which not only effectively enhances the physical and chemical bonding between the shed materials, but also the interface contact area between EPDM rubber and the nanoparticles acts as an efficient charge trap and energy dissipation center, which can quickly capture and disperse charges in partial discharge events, effectively inhibiting the accumulation of charges and the expansion of discharge, thereby improving the corona resistance of the shed. At the same time, through the designed fiber-powder bonding material, the tourmaline powder is etched by HF solution, the surface roughness is optimized, and the combination with polyester fiber is more closely formed, forming a network of efficient discharge channels. These channels can guide the discharge energy to be released along a predetermined path, reduce the direct impact on the material structure, and thus greatly improve the corona resistance of the shed. By adding semi-carbonized straw powder, the semi-carbonized straw powder is dispersed on the discharge channel network path during the preparation of the shed. When the local discharge current is released along the conductive channel network, resistance heat is generated, thereby converting part of the electrical energy into thermal energy to achieve energy dissipation. As a result, the discharge energy is gradually dissipated during the release process along the conductive channel network, reducing the direct impact of the discharge energy on the rubber matrix, thereby helping to synergistically improve the corona resistance of the shed material with the fiber-powder bonding material.
[0047] 2. In the preparation process of the fiber-powder bonding material, the present application uses HF solution to perform moderate etching treatment on the tourmaline powder, which not only retains the original physical and chemical properties of the tourmaline powder, but also significantly improves its bonding strength with polyester fiber and acrylic adhesive by increasing the surface roughness. In addition, the addition of β-alanine solution ensures the uniform distribution of the fiber-powder bonding material in the EPDM rubber, avoids agglomeration, and improves the overall performance of the material in a balanced manner. Not only does it ensure the mechanical strength of the shed material, but it also further optimizes the construction of the discharge channel network, so that the composite insulator can exhibit more stable and reliable electrical performance when subjected to complex and changeable electric field environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is a structural schematic diagram of a composite insulator according to Example 1 of the present application.
[0049] Explanation of the reference numerals: 1. core tube; 2. polypropylene foam material; 3. end flange; 4. umbrella skirt. DETAILED DESCRIPTION
[0050] The present application is further described in detail below with reference to the embodiments.
[0051] Preparation example of fiber-powder bonding material
[0052] Preparation Example 1
[0053] A fiber-powder bonding material is prepared by the following method:
[0054] a. Immerse the tourmaline powder in the HF solution, heat it to 60°C, stir and react for 5 hours, then filter the mixed solution, take the solid phase and dry it to obtain the pre-treated powder; wherein the tourmaline powder is calcium magnesium tourmaline powder with an average particle size of 700 μm; the mass concentration of the HF solution is 15%.
[0055] b. Add 1 kg of pretreated powder and 0.7 kg of polyester fiber into acrylic adhesive and carry out ultrasonic treatment for 10 min. Then heat to 40°C, stir for 2 h and filter. Take the solid phase and cure it at 50°C for 1 h to obtain a fiber-powder bonding material.
[0056] Preparation Example 2
[0057] A fiber-powder bonding material is prepared by the following method:
[0058] a. Immerse the tourmaline powder in the HF solution, heat it to 65°C, stir and react for 4 hours, then filter the mixed solution, take the solid phase and dry it to obtain the pre-treated powder; wherein the tourmaline powder is calcium magnesium tourmaline powder with an average particle size of 700 μm; the mass concentration of the HF solution is 17%.
[0059] b. Add 1 kg of pretreated powder and 0.8 kg of polyester fiber into acrylic adhesive and carry out ultrasonic treatment for 10 minutes. Then heat to 45°C, stir for 2.5 hours and filter. Take the solid phase and cure it at 55°C for 1.5 hours to obtain a fiber-powder bonding material.
[0060] Preparation Example 3
[0061] A fiber-powder bonding material is prepared by the following method:
[0062] a. Immerse the tourmaline powder in the HF solution, heat it to 70°C, stir and react for 3 hours, then filter the mixed solution, take the solid phase and dry it to obtain the pre-treated powder; wherein the tourmaline powder is calcium magnesium tourmaline powder with an average particle size of 700 μm; the mass concentration of the HF solution is 18%.
[0063] b. Add 1 kg of pretreated powder and 1 kg of polyester fiber into acrylic adhesive and carry out ultrasonic treatment for 10 minutes. Then heat to 50°C, stir for 3 hours and filter. Take the solid phase and cure it at 60°C for 2 hours to obtain a fiber-powder bonding material.
[0064] Preparation Example 4
[0065] A fiber-powder bonding material, which differs from Preparation Example 3 in that step a is not performed, and in step b, calcium magnesium tourmaline powder is directly used instead of pre-treated powder to participate in the preparation.
[0066] Preparation Example 5
[0067] A fiber-powder bonding material, which is different from Preparation Example 3 in that the tourmaline powder in this Preparation Example is ferro-tourmaline powder.
[0068] Preparation example of semi-carbonized straw powder
[0069] The straw raw material used for the semi-carbonized straw powder in the present application is rice straw. In other schemes, wheat straw, corn straw, etc. can also be selected. The type of straw raw material is not a limitation to the present application.
[0070] Preparation Example 6
[0071] Semi-carbonized straw powder is prepared by the following method:
[0072] The straw was heated at 200°C and an oxygen concentration of 1% for 3 h, and then the heated straw was crushed and sieved to obtain semi-carbonized straw with an average particle size of 200 μm.
[0073] Preparation Example 7
[0074] Semi-carbonized straw powder is prepared by the following method:
[0075] The straw was heated at 205°C and an oxygen concentration of 3% for 2.5 h, and then the heated straw was crushed and sieved to obtain semi-carbonized straw with an average particle size of 200 μm.
[0076] Preparation Example 8
[0077] Semi-carbonized straw powder is prepared by the following method:
[0078] The straw was heated at 210°C and an oxygen concentration of 5% for 2 h, and then the heated straw was crushed and sieved to obtain semi-carbonized straw with an average particle size of 200 μm.
[0079] Preparation Example 9
[0080] The semi-carbonized straw powder is different from that in Preparation Example 8 in that the straw heating temperature is 250°C.
[0081] Preparation Example 10
[0082] The semi-carbonized straw powder is different from that in Preparation Example 8 in that the oxygen concentration is 20%.
[0083] Example
[0084] Example 1
[0085] Reference Figure 1 A composite insulator includes a core tube 1, an end flange 3 and an shed 4. The core tube 1 is a ceramic core tube 1, and the core tube 1 is filled with a polypropylene foam material 2. The end flange 3 is a ceramic material, and two end flanges 3 are provided. The end flange 3 is located at the end of the core tube 1 and is coaxially threaded with the core tube 1. The end flange 3 is used to seal the end of the core tube 1 to prevent the polypropylene foam material 2 in the core tube 1 from absorbing water or falling off. The shed 4 is wrapped and sleeved on the surface of the core tube 1.
[0086] The raw material dosage of the umbrella skirt is as shown in Table 1, wherein: the fiber-powder bonding material is the fiber-powder bonding material prepared in Preparation Example 1; the semi-carbonized straw powder is the semi-carbonized straw powder prepared in Preparation Example 6; the mass concentration of the β-alanine solution is 5%; the vulcanizing agent is selected from diisopropylbenzene peroxide; and the compatibilizer is selected from ethylene-vinyl acetate.
[0087] A composite insulator is prepared by the following method:
[0088] S1, putting EPDM rubber, fiber-powder bonding material, semi-carbonized straw powder, nano-silicon dioxide and nano-alumina into a high-speed mixer, mixing for 5 minutes, then adding β-alanine solution, vulcanizing agent and compatibilizer into the high-speed mixer, and continuing to mix for 3 minutes to obtain a premix;
[0089] S2, sending the premix into an internal mixer for plastication to obtain a rubber mixture, and then sending it into an extruder to form a shed preform, and then adding the shed preform into a vulcanizer for vulcanization to obtain a shed;
[0090] S3. Fill the core tube with polypropylene foam material, and then seal both ends of the core tube with end flanges. Then clean the surface of the core tube, and then evenly apply adhesive on the surface of the core tube. Then cover the core tube with umbrella skirts and compact it. After natural drying, the composite insulator is obtained.
[0091] Example 2
[0092] A composite insulator, which differs from Example 1 in that the raw materials and dosage of the shed are different. Specifically, the raw material dosage of the shed is as shown in Table 1, wherein: the fiber-powder bonding material is the fiber-powder bonding material prepared in Preparation Example 2; the semi-carbonized straw powder is the semi-carbonized straw powder prepared in Preparation Example 7; the mass concentration of the β-alanine solution is 8%; the vulcanizing agent is selected from diisopropylbenzene peroxide; and the compatibilizer is selected from ethylene-vinyl acetate.
[0093] A composite insulator is prepared by the following method:
[0094] S1, putting EPDM rubber, fiber-powder bonding material, semi-carbonized straw powder, nano-silicon dioxide and nano-alumina into a high-speed mixer, mixing for 6 minutes, then adding β-alanine solution, vulcanizing agent and compatibilizer into the high-speed mixer, and continuing to mix for 4 minutes to obtain a premix;
[0095] S2, sending the premix into an internal mixer for plastication to obtain a rubber mixture, and then sending it into an extruder to form a shed preform, and then adding the shed preform into a vulcanizer for vulcanization to obtain a shed;
[0096] S3. Fill the core tube with polypropylene foam material, and then seal both ends of the core tube with end flanges. Then clean the surface of the core tube, and then evenly apply adhesive on the surface of the core tube. Then cover the core tube with umbrella skirts and compact it. After natural drying, the composite insulator is obtained.
[0097] Example 3
[0098] A composite insulator, which is different from Example 1 in that the raw materials and dosage of the shed are different. Specifically, the raw material dosage of the shed is as shown in Table 1, wherein: the fiber-powder bonding material is the fiber-powder bonding material prepared in Preparation Example 3; the semi-carbonized straw powder is the semi-carbonized straw powder prepared in Preparation Example 8; the mass concentration of the β-alanine solution is 12%; the vulcanizing agent is selected from diisopropylbenzene peroxide; and the compatibilizer is selected from ethylene-vinyl acetate.
[0099] A composite insulator is prepared by the following method:
[0100] S1, putting EPDM rubber, fiber-powder bonding material, semi-carbonized straw powder, nano-silicon dioxide and nano-alumina into a high-speed mixer, mixing for 8 minutes, then adding β-alanine solution, vulcanizing agent and compatibilizer into the high-speed mixer, and continuing to mix for 5 minutes to obtain a premix;
[0101] S2, sending the premix into an internal mixer for plastication to obtain a rubber mixture, and then sending it into an extruder to form a shed preform, and then adding the shed preform into a vulcanizer for vulcanization to obtain a shed;
[0102] S3. Fill the core tube with polypropylene foam material, and then seal both ends of the core tube with end flanges. Then clean the surface of the core tube, and then evenly apply adhesive on the surface of the core tube. Then cover the core tube with umbrella skirts and compact it. After natural drying, the composite insulator is obtained.
[0103] Table 1 Amount of each raw material used in the shed in Examples 1-3 (kg)
[0104]
[0105] Example 4
[0106] A composite insulator is different from Example 1 in that the fiber-powder bonding material in the shed raw material of this embodiment is the fiber-powder bonding material prepared in Preparation Example 4, and the remaining raw materials and the preparation method of the composite insulator are the same as those in Example 1.
[0107] Example 5
[0108] A composite insulator is different from Example 1 in that the fiber-powder bonding material in the shed raw material of this embodiment is the fiber-powder bonding material prepared in Preparation Example 5, and the remaining raw materials and the preparation method of the composite insulator are the same as those in Example 1.
[0109] Example 6
[0110] A composite insulator, which differs from Example 1 in that the semi-carbonized straw powder in the shed raw material of this embodiment is the semi-carbonized straw powder prepared in Preparation Example 9, and the remaining raw materials and the preparation method of the composite insulator are the same as those in Example 1.
[0111] Example 7
[0112] A composite insulator, which differs from Example 1 in that the semi-carbonized straw powder in the shed raw material of this embodiment is the semi-carbonized straw powder prepared in Preparation Example 10, and the remaining raw materials and the preparation method of the composite insulator are the same as those in Example 1.
[0113] Comparative Example
[0114] Comparative Example 1
[0115] A composite insulator is different from Example 1 in that an equal amount of calcium magnesium tourmaline powder is used in the shed raw material in this comparative example to replace the fiber-powder bonding material prepared in Preparation Example 1.
[0116] Comparative Example 2
[0117] A composite insulator, which is different from Example 1 in that: no β-alanine solution is added to the shed raw material in this comparative example.
[0118] Comparative Example 3
[0119] A composite insulator, which is different from Example 1 in that: nano silicon dioxide and nano aluminum oxide are not added to the shed raw materials in this comparative example.
[0120] Comparative Example 4
[0121] A composite insulator is different from Example 1 in that an equal amount of straw powder is used in the shed raw material of this comparative example instead of semi-carbonized straw powder.
[0122] Performance testing
[0123] Test 1 Corona resistance test
[0124] The sheds obtained in step S2 when preparing the composite insulators in Examples 1-7 and Comparative Examples 1-4 were used as test samples, and the corona resistance performance of the test samples was tested. The test results are shown in Table 2.
[0125] Experiment 2: Tensile strength test
[0126] The tensile strength of the shed obtained in step S2 was tested by a universal tensile testing machine according to the method specified in GB / T528-2009, wherein the tensile rate was 500 mm / min, the test temperature was 23°C, the sample size was 25 mm in length and 6 mm in width, and the test results are shown in Table 3.
[0127] Table 2 Corona resistance test results of sheds in Examples 1-7 and Comparative Examples 1-4
[0128]
[0129] In Examples 1-3, the corona resistance of the shed is significantly improved by introducing nano-silicon dioxide and nano-alumina, semi-carbonized straw powder, and a fiber-powder bonding material formed by combining tourmaline powder etched with HF solution and polyester fiber. This is mainly reflected in the extension of the corona aging time. Even at a higher pulse amplitude, the shed of the embodiment can withstand a longer time without performance degradation. In actual work, the shed of the composite insulator provided by the present application can quickly capture and disperse charges in a partial discharge event, effectively inhibiting the accumulation of charges and the extension of discharge, thereby helping to extend the service life of the composite insulator.
[0130] Comparing Examples 4-5 with Examples 1-3, it can be seen that when using tourmaline powder without etching treatment (Example 4) or changing the type of tourmaline powder (Example 5), the corona resistance of the shed is reduced. This confirms the importance of etching treatment for improving bonding strength and charge dispersion efficiency, and also shows the applicability of calcium magnesium tourmaline powder in this application.
[0131] By comparing Examples 6-7 with Examples 1-3, it can be seen that the semi-carbonized straw powder obtained by excessive carbonization (Preparation Example 9) or high oxygen concentration carbonization (Preparation Example 10) has a shed with a corona resistance that is still better than that of the comparative example, but is somewhat lower than that of Examples 1-3. This indicates that the semi-carbonization treatment conditions of the straw powder have a key influence on the performance of the semi-carbonized straw powder, and excessively carbonized straw powder will lead to a decrease in the final corona resistance of the shed.
[0132] The raw material of the shed in Comparative Example 1 uses tourmaline powder that is not bonded with polyester fiber. The final test results show that the corona resistance of the shed in Comparative Example 1 is much lower than that of Examples 1-3, indicating that the fiber-powder bonding material formed by combining polyester fiber and tourmaline powder plays an important role in improving the corona resistance of the shed.
[0133] By comparing Example 1 with Comparative Example 2, it can be seen that the addition of β-alanine solution helps to reduce the agglomeration of the fiber-powder bonding material in the EPDM rubber, thereby improving the overall performance of the material. The final test results show that the corona resistance of the shed of Comparative Example 2 is significantly lower than that of Example 1.
[0134] No nano-silicon dioxide and nano-alumina were added to the raw materials of the shed in Comparative Example 3. The final test results showed that the corona resistance of the shed in Comparative Example 3 was also lower than that of Examples 1-3, indicating that the introduction of nanoparticles plays a key role in improving the charge dispersion ability of the material and inhibiting charge accumulation.
[0135] The raw material of the shed in Comparative Example 4 uses untreated straw powder. Since the untreated straw powder is not conductive, it is not conducive to the transmission of discharge current in the shed raw material, which leads to a decrease in the corona resistance of the shed.
[0136] Table 3 Tensile strength test results of sheds in Examples 1-7 and Comparative Examples 1-4
[0137]
[0138] The tensile strength values of Examples 1-7 are all concentrated between 8.52-8.66 MPa, showing relatively high stability and good tensile strength.
[0139] In the shed raw material of Comparative Example 1, calcium magnesium tourmaline powder was directly used without adding polyester fiber, which eventually led to a decrease in the tensile strength of the shed material. In Comparative Example 2, no β-alanine solution was added to the shed raw material, which made it difficult for the fiber-powder bonding material to be evenly dispersed in the raw material system, which eventually led to a significant decrease in the tensile strength of the shed. In Comparative Example 4, untreated straw powder was used as the shed raw material. Compared with semi-carbonized straw powder, the uncarbonized straw powder showed disadvantages in density, hardness and strength, which eventually led to a decrease in the tensile strength of the shed material.
[0140] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A composite insulator, characterized in that: include: A core tube (1), wherein the core tube (1) is filled with a polypropylene foam material (2); An end flange (3), the end flange (3) being located at the end of the core tube (1) and being coaxially connected to the core tube (1), the end flange (3) being used to seal the end of the core tube (1); An umbrella skirt (4), wherein the umbrella skirt (4) is wrapped around the surface of the core tube (1); The umbrella skirt (4) comprises the following raw materials in parts by weight: 30-50 parts of EPDM rubber; 5-8 parts of fiber-powder bonding material; 8-10 parts of β-alanine solution; 2-5 parts of semi-carbonized straw powder; Nano silicon dioxide 0.1-0.3 parts; Nano-alumina 0.1-0.3 parts; 1-3 parts of vulcanizing agent; 1-3 parts of compatibilizer; The fiber-powder bonding material is obtained by bonding polyester fiber to the surface of tourmaline powder; The semi-carbonized straw powder is obtained by subjecting the straw to low-oxygen heating treatment at a semi-carbonization temperature, followed by crushing and screening; The fiber-powder bonding material is prepared by the following method: a. Immerse the tourmaline powder in the HF solution, heat it to 60-70°C, stir and react for 3-5 hours, then filter the mixed solution, take the solid phase and dry it to obtain the pretreated powder; b. Add the pretreated powder and polyester fiber to the acrylic adhesive for ultrasonic treatment, then heat to 40-50°C, stir for 2-3 hours, filter, and cure the solid phase at 50-60°C for 1-2 hours to obtain a fiber-powder bonding material.
2. A composite insulator according to claim 1, characterized in that: The tourmaline powder is preferably calcium magnesium tourmaline powder, and the average particle size of the calcium magnesium tourmaline powder is 700 μm.
3. A composite insulator according to claim 1, characterized in that: The mass concentration of the HF solution in step a is 15%-18%.
4. A composite insulator according to claim 1, characterized in that: The mass ratio of the pretreated powder to the polyester fiber in step b is 1:(0.7-1).
5. A composite insulator according to claim 1, characterized in that: The semi-carbonized straw powder is prepared by the following method: The straw is heated at 200-210°C and an oxygen concentration of 1%-5% for 2-3 hours, and then the heated straw is crushed and sieved to obtain semi-carbonized straw with an average particle size of 200 μm.
6. A composite insulator according to claim 1, characterized in that: The mass concentration of the β-alanine solution is 5%-12%.
7. A composite insulator according to claim 1, characterized in that: The vulcanizing agent is selected from dicumyl peroxide.
8. A composite insulator according to claim 1, characterized in that: The compatibilizer is selected from ethylene vinyl acetate.
9. A method for preparing a composite insulator according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, put EPDM rubber, fiber-powder bonding material, semi-carbonized straw powder, nano-silicon dioxide and nano-alumina into a high-speed mixer, mix for 5-8 minutes, then add β-alanine solution, vulcanizing agent and compatibilizer into the high-speed mixer, and continue mixing for 3-5 minutes to obtain a premix; S2, feeding the premix into an internal mixer, performing plasticizing at a temperature of 190-200° C. to obtain a rubber mixture, and then feeding the premix into an extruder to form a shed preform, and then adding the shed preform into a vulcanizer, performing vulcanization treatment at a temperature of 150-160° C. to obtain a shed; S3. Fill the core tube with polypropylene foam material, and then seal both ends of the core tube with end flanges. Then clean the surface of the core tube, and then evenly apply adhesive on the surface of the core tube. Then cover the core tube with umbrella skirts and compact it. After natural drying, the composite insulator is obtained.
Citation Information
Patent Citations
Preparation method of silicone rubber umbrella skirt of composite insulator
CN105885431A
Insulator and preparation method and application thereof
CN115458251A